2017
DOI: 10.1038/srep41598
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide Regulatory Roles of the C2H2-type Zinc Finger Protein ZNF764 on the Glucocorticoid Receptor

Abstract: The C2H2-type zinc finger protein ZNF764 acts as an enhancer for several steroid hormone receptors, and haploinsufficiency of this gene may be responsible for tissue resistance to multiple steroid hormones including glucocorticoids observed in a patient with 16p11.2 microdeletion. We examined genome-wide regulatory actions of ZNF764 on the glucocorticoid receptor (GR) in HeLa cells as a model system. ZNF764-and GR-binding sites demonstrated similar distribution in various genomic features. They positioned pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 59 publications
0
15
0
2
Order By: Relevance
“…The human GRα-expressing pRShGRα and its control pRSerbA −1 , and pGR107 that expresses the human GRα under the control of the SP6 promoter were gifts from R. M. Evans (Salk Institute, La Jolla, CA). pGEX-4T3-GRα full-length (FL), NTD, DBD, and LBD, which express corresponding portions of the human GRα fused with GST were previously reported (Nader, Chrousos and Kino, 2009, Fadda, Syed, Mackeh et al, 2017). pEGFP-C1-GRα, which expresses the human GRα N-terminally fused with enhanced green fluorescent protein (EGFP), was also previously reported (Habib, Sadoun, Nader et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The human GRα-expressing pRShGRα and its control pRSerbA −1 , and pGR107 that expresses the human GRα under the control of the SP6 promoter were gifts from R. M. Evans (Salk Institute, La Jolla, CA). pGEX-4T3-GRα full-length (FL), NTD, DBD, and LBD, which express corresponding portions of the human GRα fused with GST were previously reported (Nader, Chrousos and Kino, 2009, Fadda, Syed, Mackeh et al, 2017). pEGFP-C1-GRα, which expresses the human GRα N-terminally fused with enhanced green fluorescent protein (EGFP), was also previously reported (Habib, Sadoun, Nader et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…ChIP was performed by using the Pierce Magnetic ChIP Kit (Pierce Inc.) in HeLa cells according to the modified instruction from the manufacturer (Fadda et al, 2017). Briefly, HeLa cells were grown on 10-cm dishes, transfected with control or SIRT1 siRNA, and were treated with or without 10 −6 M of DEX similar to the samples for RNA-seq.…”
Section: Methodsmentioning
confidence: 99%
“…128 In a genome-wide binding study using ChIP-sequencing in human HeLa cells, ZNF764- and GR-binding sites are found in close proximity, indicating that ZNF764 modulates GR transcriptional activity by incorporated in the transcriptional complex formed on DNA-bound GR. 129 The exact physiologic functions of ZNF764 in humans are not known, but it appears to regulate the GR activity involved in the stress response organized by the hypothalamic-pituitary-adrenal axis and the AR activity required for fetal development of male-type external genitalia. 128…”
Section: Krab-znfsmentioning
confidence: 99%
“…Recently, we demonstrated a label-free, SERS based approach for the analysis of erythrocytes membranes 12 , in which unlabelled cells were put in contact with a high uniform and densely packed SERS substrate. Clearly, due to the short-range response of the SERS mechanism 13 , only bio-molecules exposed on the membrane can be efficiently detected, conferring a high-contrast with respect to the bulk Raman contribution 1416 . It is worth noticing that the spatial uniformity of the plasmonic substrate enhancement factor (EF) 17 is a crucial parameter of such type of investigation, minimising the intrinsic signal fluctuations in SERS imaging 12 .…”
Section: Introductionmentioning
confidence: 99%